Does Emotional Intelligence of Dental Undergraduates Influence Their Patient Satisfaction? - Mandakini Mohan; Kah Heng Lin; Abhishek Parolia; Allan Pau (International Journal of Dentistry)
Objectives. The research aimed to investigate if emotional intelligence (EI) scores of dental undergraduates influenced their patients’ satisfaction with the treatment received. Methods. A 33-item EI questionnaire was completed by 46 dental undergraduates in a cross-sectional study. Responses, measured on a five-point Likert scale, were summed to yield EI scores. Patients treated by the same undergraduates were invited to complete a patient satisfaction (PS) questionnaire. EI and PS scores were calculated and compared by undergraduates’ gender and the patients’ age and education status. The four EI factors (optimism/mood regulation, appraisal of emotions, utilization of emotions, and social skills of students) were correlated with PS using Spearman’s correlation test with a significance level set at p<0.05. Results. EI scores did not differ significantly between male (N = 23) and female (N = 23) undergraduates p=0.218. PS was not associated with patients’ gender, but those educated to the secondary school level were more likely to be satisfied compared to those educated to the college/university level p=0.022. Of the four EI factors, optimism/mood regulation was positively correlated with PS p=0.049. Conclusion. The results of the study suggest that the EI of the students can influence PS. Practical Implications. Interventions to enhance EI can be developed to improve the patient experience.